Danish Archaeology in the 1980's - beyond theoretical poverty? - Mahler, Ditlev; Paludan-Müller, Carsten; Stumman, Steffen (Journal of Danish Archaeology, 1984)
Danish Archaeology in the 1980's - beyond theoretical poverty?